Double input Z-source inverter applicable in dual-star PMSG based wind turbine. (November 2016) - Dehghanzadeh, Ali Reza; Behjat, Vahid; Banaei, Mohamad Reza
Highlights: A new double-input Z-source inverter for application in wind energy conversion system (WECS) is proposed. Dual-star PMSG is utilized as a gear less generator wind energy conversion system (WECS). Proposed WECS results reduction of converter components and reliability against short circuit. Simulation and experimental results validates the ability of proposed structure. Abstract: This paper proposes a new double-input Z-network for application in wind energy conversion system (WECS) which is composed of two same DC voltage sources as input sources, two inductors and one capacitor. As a result, the presented structure requires less capacitor number compared to traditional Z-network and it will be able to deliverer energy of both DC sources to local load or grid. The proposed inverter is applicable in dual-star PMSG based WECS, since it requires two DC voltage sources in same value. Besides, dynamic modeling of dual-star PMSG is presented to analyze proposed WECS connected to grid which employs dual-star PMSG and double-input Z-source inverter. The proposed dual-input Z-source inverter controls maximum power point tracking (MPPT) and delivering power to the grid. Therefore, other DC–DC chopper is not required to control two sets of rectified output voltage of generator in view of MPPT. As a result, the proposed topology requires less power electronic switches and the suggested system is more reliable against short circuit. The ability of proposed WECS with dual-star PMSG and double-input Z-source inverter is validated with simulation results and experimental tests using PCI-1716 data acquisition system.